Prototype of Automatic Water Sprayer Based on Humidity Sensor and ATmega8 AVR Microcontroller in Oil Palm Nurseries - Marcelo Salas Sihombing; Suhada Suhada; Ika Purnama Sari (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2022)
Oil palm nurseries are currently experiencing very rapid development, but the watering process at the oil palm nursery stage itself is still done manually so that it is less efficient in the watering process. To overcome these problems, in this study an automatic system was created using the AVRATmega8 microcontroller as the main controller of the system. With the variable humidity of the planting media as a timer for watering, a prototype water sprayer is made that can do watering automatically. The prototype of this automatic water sprayer is equipped with a soil moisture sensor which is used to read the moisture value of the oil palm growing media as well as functioning as a system input, LCD as a medium for monitoring system performance, and a relay that functions to turn on and off the water pump connected to the installation of the planting media watering pipe. . Watering of oil palm seedlings is carried out when the soil moisture sensor detects that the moisture value in the planting media has been below the lower limit of the working system and stops watering when the sensor readings indicate that the humidity value of the planting medium is above the upper limit of the working system.